Rearing of Humpback Grouper (Cromileptes altivelis) Fed on Pellet and Trash Fish in Cage Culture System - Fauzi, I.A.; Mokoginta, I.; Yaniharto, D. (Indonesian Society of Scientific Aquaculture (ISSA), 2008)
This experiment was conducted in order to have comparative description about the growth of humpback grouper (Cromileptes altivelis) fed by artificial diets compare to the trash fish in cage culture system. The protein level of the artificial diet was 42.5%, and the trash fish was 51-70%. Fish fed on the experimental diet twice a day, at satiation, for 60 days. Result showed that the growth rate of fish fed on the artificial diet are slightly lower (6.37% and 8.38%) than that of trash fish (11.11% and 10.18%). Though the growth levels are lower, the feed conversion ratio (3.55 and 3.13) showed a better value than that of fish fed on trash fish (4.81 and 5.83). The use of artificial feed is also more economical than trash fish feed based on cost of the feed. With that fact we can conclude that artificial feed can equalize or even substitute the trash fish feed for Humpback grouper rearing in cage culture system. Keywords: artificial diets, cage culture, humpback grouper, Cromileptes altivelis ABSTRAK Penelitian ini dilakukan untuk mengetahui pertumbuhan ikan kerapu bebek (Cromileptes altivelis) antara yang diberi pakan buatan dan ikan rucah, yang dipelihara pada keramba jaring apung. Kadar protein pakan buatan adalah 42,5%, dan ikan rucah adalah 51-70%. Ikan diberi pakan 2 kali sehari, secara satiasi, selama 60 hari pemeliharaan. Hasil penelitian menunjukkan bahwa laju pertumbuhan ikan yang diberi pakan buatan lebih rendah (6,37% dan 8,38%) dibandingkan dengan yang diberi ikan rucah (11,11% dan 10,18%). Meskipun laju pertumbuhan lebih rendah, konversi pakannya (3,55 dan 3,13) lebih baik dibandingkan dengan ikan yang diberi pakan berupa ikan rucah (4,81 dan 5,83). Berdasarkan biaya untuk pakan, penggunaan pakan buatan lebih ekonomis dibandingkan ikan rucah. Dengan demikian, pakan buatan dapat menggantikan ikan rucah dalam pemeliharaan ikan kerapu bebek di keramba jaring apung. Kata kunci: pakan buatan, keramba jaring apung, ikan kerapu bebek, Cromileptes altivelis